Nanoparticles behaviors in porous media: Application to enhanced oil recovery - Foroozesh, J. (Elsevier B.V., 2020)
Stability of nanofluids along with their promising properties has led to wide applications of nanoparticles (NPs) in enhanced oil recovery (EOR) projects. Nanofluids that are colloidal suspension of NPs in base fluids, can stay stable at harsh reservoir conditions where other chemical-EOR solutions made of surfactants and polymers start degrading and lose their stabilities and functionalities. Specific surface characteristics of NPs have made them to affect fluids and rock properties and their pair interactions in porous media in favor of EOR mechanisms. Nevertheless, applying NPs in subsurface projects needs a strong understanding of NPs behaviors and their functions in porous media. As such, this work aims to give deeper insight into NPs functionality in porous media needed for practical design of NPs-EOR projects. This review endeavors to analyze the nanoparticle behaviors in porous media in view of criteria needed for application in EOR subsurface projects. Different promising mechanisms for NPs assisted EOR followed by controlling factors to optimize the EOR efficiency are deliberated. Effect of interparticle interactions along with other hydrodynamic forces on dispersion stability, nanoparticle agglomerations and subsequent settling have been analyzed in order to prepare stable nanofluid(s) for their further implications in EOR. Transport of NPs through porous media with the associated challenges is also investigated. Recent studies on NPs assisted EOR techniques are also presented. Finally, EOR challenges using NPs and the needed future research are highlighted. Â© 2020 Elsevier B.V.